PROFILE OF STUDENTS' CONCEPTIVE UNDERSTANDING IN FRACTIONS AT SMP MUHAMMADIYAH BANDA ACEH - Nuralam Syamsuddin; Khairina Khairina; Zahara Mustika; Sabaruddin Sabaruddin (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2022)
Students find mathematics boring to study because it is thought to be difficult for them to understand, particularly when it comes to arithmetic operations, symbols, and a variety of abstract formulas. The challenge in working with fractions is equal the denominator throughout addition and subtraction operations. This study's goal was to identify the types and causes of student difficulty in the content for fractional arithmetic operations. Descriptive research is used in this study. All class VII students make up the population, and there were a total of 17 participants sampled. a tool with an interview guide and written test. Six students were chosen for interviews based on the test results that have been examined. The results showed that the students' level of difficulty was 29.41 percent, moderate difficulty was 5.88 percent, high difficulty was 41.18 percent, and very high difficulty was 23.53 percent. The types of difficulties experienced by students in using concepts and principles ranged from 26.47 percent to 64.71 percent, and difficulties in using verbal were as high as 14.71 percent. It was determined that children were still having trouble grasping the idea of fractions.